Re-thinking Neutrality Through Emotional Labour: The (In)visible Work of Conference Interpreters - Ayan, Irem (TTR)

(untitled) (Association canadienne de traductologie, 2020)
Relying upon a combination of ethnomethodological and sociological tools provided by Hochschild’s (2003 [1983]) theory of emotional labour, this article examines the concept of the interpreter’s neutrality as a form of feeling management at work which requires interpreters to align their behaviours with the norms shaping each interpreting setting. Drawing on the interviews conducted between March and August 2018 with twenty-one interpreters working in various social, cultural, and institutional settings, the study describes the interpreter’s emotional labour in the context of conference interpreting, and argues that the interpreter’s actual task of becoming the voice of the speaker intrinsically involves emotional labour. Achieving neutrality entails suppressing personal beliefs and displaying certain emotions which may not always be genuine in some contexts, and tending to the needs of clients in others. The conceptual framework of emotional labour offers an important analytical tool to re-visit theoretically and empirically not only the notion of the interpreter’s neutrality from a critical perspective, but also the incoherence of professional codes of practice, which oftentimes leaves interpreters in a practical and ethical quandary.